Always Read the Label Carefully (Before Replacing). Issue 5 (1st October 2002) - Bindoff, Laurence
Abstract : I must admit that my first reactions on being asked to contribute to this section were negative. I felt I might be damned if I did (litigation or ridicule) and damned if I did not (something to hide). I accepted the task therefore with some apprehension. The learning experience I would like to share concerns a common neurological condition and the issue of diagnostic labelling. The error, if that is indeed what it was, I have made more than this once and I am not sure that I will not transgress again. The patient was 68 years old when I first saw him. He was referred because of tremor present for around 17 years, as well as involuntary movements of his right arm of more recent onset. He had been seen by a neurologist in another region many years previously and diagnosed as having an essential tremor. This diagnosis was